Survey Kekuatan Otot Lengan Pada Tim Handball Kota Pekalongan - Ra’uf Pasha, Achnaf; Tresnowati, Idah; Widya Putri, Mega; Riski Adi Wijaya, M (Jurnal Muara Olahraga, 2025)
The purpose of this study was to describe the arm muscle strength of handball players in Pekalongan City, as assessed using a push-up test. Based on the survey results, the arm strength of these players was largely in the poor category. When broken down by gender, both the men's and women's teams showed inadequate results. The findings of this study can motivate coaches and sports practitioners, as well as members of handball organizations, to analyze arm muscle strength in this sport. From observations and interviews conducted with the Pekalongan City Handball Team, it was discovered that training takes place every Tuesday, Thursday, and Saturday. The focus of the training sessions provided by the coaches primarily revolves around skills such as passing, shooting, movement, and competitive play. This training format was chosen to improve physical skills while making the sport more engaging and enjoyable for the athletes. The research design used in this study is a quantitative descriptive design. This study will utilize a survey method to collect data on the arm muscle strength of the Pekalongan City handball team. This quantitative descriptive study utilizes a one-time testing method, where the assessment is only conducted once. This approach was applied to draw a sample from the existing population for this study. This research will be conducted on the Pekalongan City Handball Team. Based on the measurement table, the arm muscle strength of the Pekalongan City Handball Team shows that 10 athletes (66.67%) are in the "Poor" category, 4 athletes (26.67%) are in the "Moderate" category, and only 1 athlete (6.67%) is in the "Good" category. This distribution shows that the "Poor" category is dominant, representing more than half of the total athletes. No athlete reached the "Very Good" or "Very Poor" category. This indicates that the majority of team members do not have the optimal arm muscle strength needed to improve their performance in handball.